CARS Comprehensive Intervention for Secondary Students With Emotional and Behavioral Problems: Conceptualization and Development. (December 2015) - Kern, Lee; Evans, Steven W.; Lewis, Timothy J.; State, Talida M.; Weist, Mark D.; Wills, Howard P.
Educating children and youth with significant social, emotional, and behavioral (SEB) problems continues to pose significant challenges for special and general educators. The long-term effects of challenges this group of students experience include school dropout, mental health problems, unemployment, and high incarceration rates. To date, the majority of research examining the efficacy of interventions and supports has been conducted at the elementary level, creating a compelling need for comprehensive examination of interventions and supports for high school students. In this article, we provide a summary of the iterative development process the Center for Adolescent Research in Schools (CARS) undertook to develop a logic model that guided development and implementation of a multi-component intervention incorporating evidence-based practices with adaptations for high school–age students. In addition, we provide an overview of a national randomized control trial, including a review and decision structure to identify multiple outcome measures, which was designed to examine the efficacy of the developed intervention logic model.